Aligning Environmental Regulations to Handling Climate Change and Biodiversity - Sibarani, Porman Augustina (KnE Social Sciences, 2025)
Climate change and biodiversity loss are interrelated global environmental challenges. Climate change is a long-term change in temperature and weather patterns over a very long period of time. The form of climate change is related to changes in weather patterns or changes in the distribution of weather events. The main cause of climate change is global warming. Biodiversity is defined as the diversity or variety of life on earth, including types of plants, animals, and microorganisms living in various ecosystems. In the relationship between climate change and biodiversity where climate change can cause species extinction, habitat changes, and ecosystem disruption. While the role of biodiversity is to overcome climate change, where ecosystems play an important role in absorbing carbon dioxide from the atmosphere and supporting resilience to the impacts of climate change. Efforts to integrate these two issues in national legislation through a comprehensive approach. Integrated regulations combine the objectives of protecting biodiversity and addressing the challenges of climate change with mitigation actions, namely reducing greenhouse gas emissions toward renewable energy such as solar, wind and hydro; increasing energy efficiency in homes, industry, and sustainable transportation; protecting forests as carbon sinks and reforestation; and reducing greenhouse gas emissions by managing waste to reduce methane emissions as well as energy-efficient building and environmental management. In addition, adapting actions to reduce vulnerabilities impacting existing climate change, such as urban planning based on climate and agricultural practices, adaptive, conservation, and habitat restoration and protection of vulnerable species. Identifying challenges and opportunities, including shifts in plant and pollinator phenology due to climate change. The main challenge is the mismatch in phenology between plants and pollinators, which can disrupt the pollination process, impact crop production, and create plant pests because rain patterns or droughts cause a decrease in crop yields, which can have an impact on economic value. While for sustainable agriculture, the government can provide incentives in the form of subsidies, taxes, and technical assistance to farmers, such as crop rotation, use of organic fertilizers, and soil conservation. To increase awareness and more integrated and effective legal action in protecting the planet, comprehensive efforts are needed, including strong regulations, stricter law enforcement, increased public awareness, and active involvement from various parties. These steps must complement each other to achieve the goal of sustainable environmental conservation.